Analisis Unsur Intrinsik dan Nilai-Nilai Pendidikan Karakter dalam Cerpen Surga Pertama Karya Zahro Syaquilla - Yolanda Tania; Eva Oktaviana Sari; Yukhsan Wakhyudi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2026)
This study aims to describe the intrinsic elements of the short story Surga Pertama by Zahro Syaquilla and to examine the character education values embodied in the work. The research employs a qualitative descriptive method, with the manuscript of Surga Pertama serving as the primary source of data. Data collection and analysis were conducted through a sociological approach to literature, focusing on the relationship between the literary structure and the social and educational values presented in the story. The intrinsic elements analyzed include theme, characterization, plot, setting, point of view, moral message, and language style. In addition, the study identifies several character education values represented through the events, characters, and messages in the short story, namely tolerance, creativity, independence, communicativeness, and responsibility. These values are reflected in the attitudes and actions of the characters as well as in the moral messages conveyed by the author. The findings are expected to provide a comprehensive understanding of how the intrinsic elements of the short story support and strengthen the delivery of character education values through literary expression.